Combination of phage therapy and cefiderocol to successfully treat Pseudomonas aeruginosa cranial osteomyelitis. Issue 3 (5th May 2022) - Simner, Patricia J.; Cherian, Jerald; Suh, Gina A.; Bergman, Yehudit; Beisken, Stephan; Fackler, Joseph; Lee, Martin; Hopkins, Robert J.; Tamma, Pranita D.
Abstract: Background: Pseudomonas aeruginosa has the ability to exhibit resistance to a broad range of antibiotics, highlighting the importance of identifying alternative or adjunctive treatment options, such as phages. Patients and methods: We report the case of a 25-year-old male who experienced an accidental electrocution resulting in exposed calvarium in the left parieto-temporal region, complicated by a difficult-to-treat P. aeruginosa (DTR- P. aeruginosa ) infection. Cefiderocol was the sole antibiotic with consistent activity against six bacterial isolates obtained from the infected region over a 38 day period. Results: WGS analysis identified a bla GES-1 gene as well as the MDR efflux pumps MexD and MexX in all six of the patient's ST235 DTR- P. aeruginosa isolates, when compared with the reference genome P. aeruginosa PA01 and a P. aeruginosa ST235 isolate from an unrelated patient. After debridement of infected scalp and bone, the patient received approximately 6 weeks of cefiderocol in conjunction with IV phage Pa14NPøPASA16. Some improvement was observed after the initiation of cefiderocol; however, sustained local site improvement and haemodynamic stability were not achieved until phage was administered. No medication-related toxicities were observed. The patient remains infection free more than 12 months after completion of therapy. Conclusions: This report adds to the growing literature that phage therapy may be a safe and effective approach to augment antibiotic therapy for patients infected with drug-resistant pathogens. Furthermore, it highlights the importance of the GES β-lactamase family in contributing to inactivation of a broad range of β-lactam antibiotics in P. aeruginosa, including ceftolozane/tazobactam, ceftazidime/avibactam and imipenem/relebactam.